When silence falls - Pinchbeck, Cara; Peacock, Amanda; Art Gallery of New South Wales (Sydney, NSW : Art Gallery of New South Wales, 2015)
This book considers the work of artists from across the globe who contemplate, investigate and respond to the inherent violence of often unacknowledged events, massacres, ethnic cleansing, cultural displacement, political force ‒ and provide a voice for those who have been silenced. The artists included share a faith that art should play its part in excavating and reimagining the past, however troubling the subject matter. While the works speak strongly of conflict, they do not lay blame. Rather, they offer a space for contemplation that is more sensual and emotive than the history writing and news imagery to which we can become desensitised. They lament loss while exploring both the suffering and survival that is humanity's common inheritance.
Artists include Vernon Ah Kee, Tony Albert, Richard Bell, Paddy Bedford, Daniel Boyd, Fiona Hall, William Kentridge, Rusty Peters, Ben Quilty, Pedro Reyes, Doris Salcedo, Timmy Timms, Hossein Valamanesh, Kara Walker and Judy Watson.
Published in conjuction with exhibition held at The Art Gallery of New South Wale, 19 December 2015 - 1 May 2016, curated by Cara Pinchbeck.
Published in association with the exhibition at the Art Gallery of New South Wales, 19 December 2015-1 May 2016
Keywords: Art Gallery of New South Wales -- Exhibitions; Art, Modern -- 21th century -- Exhibitions; Life change events in art -- Exhibitions; Violence in art -- Exhibitions; Life change events -- In art -- Exhibitions; Art, Modern -- 21st century -- Exhibitions; Art - Catalogues; Race relations - Attitudes; Colonisation; Race relations - Violent; Race relations - Power relations; History; Race relations - Violent - Massacres, murders, poisonings etc. - To 1900.; Art; Art - Exhibitions; Australia; Australian